Spicer & Pegler's Income tax and profits tax - Spicer, Ernest Evan.; Pegler, Ernest Charles; Carmichael, Keith Stanley; Great Britain (London : H.F.L., 1966)
The book deals with the subject matter of taxation.
First ed. published in 1907 under title: Income tax in relation to accounts.
Includes legislation and index.
Kept up to date by supplements.
rpm 25/01/2019
Loans
Keywords: Income tax; Business tax